Documentation of torture and the Istanbul Protocol: Applied medical ethics - Frewer, Andreas; Furtmayr, Holger (Medicine Health Care and Philosophy, 2010)
The so-called Istanbul Protocol, a Manual on the Effective Investigation and Documentation of Torture and other Cruel, Inhumane or Degrading Treatment or Punishment was adopted by the United Nations soon after its completion in 1999 and since then has become an acknowledged standard for documenting cases of alleged torture and other forms of severe maltreatment. In 2009 the "Forum for medicine and human rights" at the Medical Faculty at the University Erlangen-Nuremburg has provided the first German edition of this manual. The article traces back the development of the protocol taking into account the general background as well as the factual occasion of its initiation. The main ethical and legal principles of the manual are introduced as well as the projects for implementing the rules provided in the protocol that have been carried out so far. From this the urgent need for implementation of the Istanbul Protocol guidelines also in Europe and in German-speaking countries and here not exclusively but especially within asylum procedures becomes clear. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2025-03-13
Keywords: Asylum; Documentation; Human rights violations; Istanbul protocol; Mistreatment; Torture; United Nations